Vocal evaluation in teachers with or without symptoms - Tavares, Elaine L. M.; Martins, Regina Helena Garcia [UNESP] (Elsevier B.V., 2007)
The aim of this study was to perform voice evaluation in teachers with and without vocal symptoms, identifying etiologic factors of dysphonia, voice symptoms, vocal qualities, and laryngeal lesions. Eighty teachers were divided into two groups: GI (without or sporadic symptoms, 40) and GII (with frequent vocal symptoms, 40). They answered a specific questionnaire, and were subject to a perceptual vocal assessment (maximum phonation time, glottal attack, resonance, coordination of breathing and voicing, pitch, and loudness), GIRBAS scale, and to videolaryngoscopy. Females were predominant in both groups, and the age range was from 36 to 50 years. Elementary teachers predominated, working in classes with 31-40 students. Voice symptoms and alterations in the perceptual vocal analysis and in the GIRBAS scale were more frequent in GII In 46 teachers (GI-16; GII-30), videolaryngoscopy exams were abnormal with the vocal nodules being the most frequent lesions. These results indicate that a teacher's voice is compromised, and requires more attention including control of environmental factors and associated diseases, preventive vocal hygiene, periodic laryngeal examinations, and access to adequate specialist treatment.
Keywords: dysphonia; teachers; voice; professional voice